Analysis of Teacher Competence Using the Madrasah Digital Report Applicationin Managing Student Learning Outcome - Frarera, Andre Nova; Nurmawati, Nurmawati; Nasution, Sahkholid (STAI Miftahul Ula Nganjuk, 2024)
The purpose of this study is to ascertain the competence of teachers in utilizing the Madrasah Digital Report Card application for managing students' learning outcomes at the Private Tsanawiyah Madrasah Hubbul Wathan Modal Bangsa, Langkat County, located on Jl. Pasar 7 Bandar Meriah, North Namu Ukur Village, Sei Bingai District, Langkat County. This qualitative research aims to understand phenomena such as behavior, perception, motivation, and expectations of subjects, aligning with the study's focus on the implementation of the Madrasah Digital Report Card application at the Tsanawiyah Madrasah Hubbul Wathan Modal Bangsa. A descriptive narrative approach was employed, analyzing collected data and providing narrative interpretation to understand experiences. The results indicate that the utilization of the Madrasah Digital Report Card application at the Private MTs Hubbul Wathan Modal Bangsa is optimized by the teachers, who exhibit strong skills in operating the application. Consequently, the implementation has led to significant progress in technology use and enhanced the professional capabilities of teachers in managing students' learning outcomes.